Multinucleon transfer in peripheral collisions of 86Kr on 208Pb at 25 MeV/nucleon - Travlou, Eleftheria; Giannitsa Chryssi,; Souliotis Georgios,; Gkatzogias Konstantinos,; Kontogianni Eirini,; Fasoula Olga,; Emannouil Theocharis,; Martin Veselsky,; Sherry Yennello,; Aldo Bonasera, (HNPS Advances in Nuclear Physics, 2026)
In this work, we study projectile-like fragments resulting from multinucleon transfer during the reaction of a 86Kr beam with a 208Pb target at 25 MeV/nucleon using experimental data obtained with the MARS spectrometer at the Cyclotron Institute of Texas A&M University in previous works of our group [2]. The data are systematically compared to theoretical model calculations. Our analysis involved two models: the Deep Inelastic Transfer model (DIT) [3] and the Constrained Molecular Dynamics model (CoMD) [4]. Additionally, the GEMINI code [5] was used to simulate the deexcitation of primary fragments. We performed mass and angular distribution analyses to gain insight into the reaction mechanism of peripheral collisions involving extensive multinucleon transfer. Both models appear to describe the behavior of the data in an overall satisfactory way.